Implementing Differentiated Instruction In Physical Education: A Phenomenological Study On Teachers’ Strategies And Students’ Experiences - Fitriana Puspa Hidasari; Doni Pranata; Muhammad Darlis; Muhammad Azlan; Edeltrudis Higaang (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Objectives. This study aimed to describe how teachers implement differentiated instruction in physical education classes and to explore students’ experiences during the learning process. Materials and Methods. This study used a qualitative phenomenological approach. The participants were three physical education teachers and fifteen junior high school students from SMPN 13, SMPN 20, and SMPN 9 in Pontianak, West Kalimantan, selected through purposive sampling. Data were gathered through in-depth interviews and field observations, with the researcher acting as the main instrument. The data were then analyzed using Colaizzi’s method to obtain systematic and in-depth findings Results. The results showed that teachers had begun to identify students’ readiness, interests, and talents through observation and initial assessment. They also prepared lesson plans and tried to deliver instruction using varied content. Assessment covered the affective, cognitive, and psychomotor domains, although greater attention was still given to psychomotor performance. Students recognized that the learning materials were varied, but they felt that the differentiated practices were still general and had not fully responded to their individual needs. The main challenges found in the study were limited facilities and infrastructure, teachers’ limited understanding of differentiated instruction, and teaching practices that were still largely teacher-centered. Conclusions. In general, the implementation of differentiated instruction in junior high school physical education is still at an early stage. Teachers have started to identify students’ learning profiles and apply variations in content and assessment across several domains. Although these practices have not yet been carried out consistently or fully adapted to individual student needs, they show an initial move toward more responsive and inclusive learning.